Sanksi Tindakan Kebiri Kimia Ditinjau dari Perspektif Hak Asasi Manusia dan Ilmu Kedokteran Kehakiman - Astari, Astri; Gultom, Jonathan Andreas Thomas; Fadli Hadiputro (Jurnal Hukum Statuta, 2021)
Sexual violence has now become a worldwide issue andmuch attention by various parties. In fact, this sexual violence oftenhappens to children. In order to prevent the occurrence of sexual violence against children is increasing. The government has issued Government Regulation Number 70 of 2020 concerning Procedures for the Implementation of Chemical Castration, Installation of Electronic Detection Devices, Rehabilitation, and Announcement of the Identity of Perpetrators of Sexual Violence against Children. However, the implementation of chemical castration is still reaping the pros and cons, especiallywithin the framework of Human Rights (HAM). In the perspective of Human Rights (HAM) the implementation of chemical castration against perpetrators by administering antiandrogen substances is considered a violation of human rights considering the many side effects that result later and making it no longer limited to punishment, but enters the realm of human rights torture that degrades human dignity. Meanwhile, in the perspective of Judicial Medicine, the Indonesian Doctors Association (IDI) refuses to be the executor of castration punishment for perpetrators of sexual crimes against children because they view that giving chemical castration to perpetrators of sexual violence against children cannot be done because of the weakening of the psychological and physical endurance of perpetrators of sexual violence against children contrary to the oath and code of ethics of the medical profession itself. So it can be concluded that the implementation of the chemical castration criminal punishment today is still reaping the pros and cons.